Protective behavioral strategies and alcohol use in Argentinean college students: Differences between the academic season and the summer break - Guzmán, María Luz (2019)
Introduction: Protective behavioral strategies (PBS) reduce or minimize the negative consequences of alcohol drinking. PBS hold promise as intervention targets to reduce alcohol use and its negative consequences and, therefore, there has been an increasing interest in assessing determinants of this variable. It has been reported that women use more PBS than men and that certain contexts/seasons (e.g., Spring break vs. the regular academic season) are associated with greater use of PBS. The great majority research assessing these effects, however, comes from U.S., and very little is known about PBS determinants in South America. Aim: This work examined seasonal variations in the use of protective behavioral strategies (PBS) and alcohol outcomes in two distinct times of the academic calendar: 1-the spring academic semester and 2-summer break. We examined -both within each time and prospectively- the relationship between the use of PBS and alcohol outcomes. Method: A sample of 223 college students reported -via two online surveys -- use of PBS, alcohol use and alcohol-related negative consequences. Results. The use of PBS (notably, the dimension “manner of drinking”) was negatively associated with alcohol outcomes, particularly in women and during spring. The frequency of use (in women only) and the weekly volume of alcohol ingested were greater during the summer. Women, but not men, reported greater use of PBS and fewer negative consequences during the summer break than at the academic season. Conclusions. The use of certain PBS may be associated, particularly in women, with lower alcohol consumption and alcohol-related negative consequences.